P2.2 RESISTANT HYPERTENSION AND STRUCTURAL ALTERATIONS OF SUBCUTANEOUS SMALL RESISTANCE ARTERIES - Claudia Agabiti Rosei; Carolina De Ciuceis; Claudia Rossini; Maria Lorenza Muiesan; Massimo Salvetti; Enzo Porteri; Alice Gavazzi; Anna Paini; Stefano Caletti; Maria Antonietta Coschignano; Paola Pileri; Enrico Agabiti Rosei; et al. (Artery Research, 2015)
Background: It is was suggested that, in resistant hypertension, the presence of particularly pronounced microvascular alterations may contribute to explain the relative lack of response to treatment. Similarly, in diabetic patients, the persistence of an altered microvascular structure, despite the administration of multiple drug combination treatment, might partly explain the difficulty to reach target blood pressure values, especially for systolic blood pressure. Patients and methods: For this reason, we investigated a population of 94 treated essential hypertensive patients. Secondary forms of hypertension were excluded according to standard clinical evaluations and biochemical or instrumental assessment, and in all patients a 24-hour blood pressure monitoring was performed in order to exclude a white coat effect. In all patients, we evaluated small resistance arteries morphology by a wire micromyographic approach (Mulvany’s technique). A small amount of subcutaneous tissue was obtained by local biopsy or during election surgery and subcutaneous small resistance arteries were dissected and mounted on a myograph; the media to lumen ratio (M/L) was then measured. Sixteen patients had true resistant hypertension, and were compared with the remaining 78 patients with non-resistant hypertension. Results: The two groups were different in terms of mean age, pulse pressure/stroke volume, media to lumen ratio and internal diameter of small resistance arteries. Conclusion: Our data suggest that hypertensive patients with true resistant hypertension have greater microvascular structural alterations compared with non-resistant hypertensive patients. This could explain, at least in part, the resistance to pharmacological treatment and the high cardiovascular risk observed in these patients.